The impact of multimorbidity on the occurrence of depression among middle-aged and elderly people in China - Biqi Zu; Peng Zhang; Ziwei Xie; Jinsong Huang; Yunan Zhang; Meiling Tang; Yulan Wu; LiJun Fan (PLoS ONE, 2026)
Objective This study aims to investigate the association between multimorbidity and the incidence of depression in the middle-aged and elderly populations in China, focusing on the impact of multiple chronic diseases on mental health outcomes. Methods This research comprises a rigorous retrospective cohort study utilizing the esteemed China Health and Retirement Longitudinal Study (CHARLS) data. Follow-up data were meticulously analyzed from 2013 (Wave 2) to 2020 (Wave 5), with data from 2015 serving as the essential baseline for examining multimorbidity and depression. We employed Directed Acyclic Graphs (DAGs) to identify potential confounding factors, applying overlap weighting to effectively mitigate their influence, thus ensuring that intergroup comparisons mirror the integrity of a randomized trial. The association between multimorbidity and depression was systematically evaluated through Cox regression models, supplemented by thorough subgroup analyses and sensitivity analyses to confirm the robustness of our findings. Results Our analysis included 3,495 participants aged 45 and older. Multimorbidity was found to significantly elevate the risk of depression (Hazard Ratio [HR] = 1.431, 95% Confidence Interval [CI] 1.202–1.703). This risk was particularly pronounced in women (HR = 1.617, 95% CI: 1.290–2.027) and older adults (HR = 1.482, 95% CI: 1.221–1.799). The risk of depression increased with the number of chronic diseases, particularly with two (HR = 1.423, 95% CI: 1.192–1.701) or three (HR = 2.045, 95% CI: 1.503–2.784) chronic conditions. However, this association diminished in significance when four chronic conditions were present (HR = 0.815, 95% CI: 0.444–1.497). Conclusion The pronounced association between multimorbidity and depression in middle-aged and elderly individuals highlights an urgent public health issue, particularly for women and older adults. This study’s use of overlap weighting provides strong evidence of the substantial impact of multimorbidity on mental health. It underscores the immediate need for targeted interventions to improve mental well-being in these vulnerable groups.